2009
DOI: 10.1080/01421590802144278
|View full text |Cite
|
Sign up to set email alerts
|

Leadership curriculum in undergraduate medical education: A study of student and faculty perspectives

Abstract: Study participants identified the necessary qualities, knowledge and skills to serve as goals for an undergraduate leadership curriculum. Future studies should address optimal methods of teaching and assessing leadership skills among medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 19 publications
4
95
0
Order By: Relevance
“…109 One report suggested that an EI competency inventory effectively assessed these skills in medical school applicants. 111 A survey of medical students and faculty suggested that both groups want EI to be a medical school competency, 133 and another small trial suggested that simulations are a good way of cultivating awareness of EI and leadership. 72 In a study that assembled a convenience sample of 64 medical students, Stratton et al 134 observed that EI decreased marginally during training, which could be mitigated by conducting workshops on EI for medical students.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…109 One report suggested that an EI competency inventory effectively assessed these skills in medical school applicants. 111 A survey of medical students and faculty suggested that both groups want EI to be a medical school competency, 133 and another small trial suggested that simulations are a good way of cultivating awareness of EI and leadership. 72 In a study that assembled a convenience sample of 64 medical students, Stratton et al 134 observed that EI decreased marginally during training, which could be mitigated by conducting workshops on EI for medical students.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…Situational learning theory suggests that adult learners in vocational courses respond particularly well to such approaches, and this may explain the positive feedback we received. This has been observed with similar leadership and management programmes in the US and UK (Quince et al, 2014;Varkey, Peloquin, Reed, Lindor, & Harris, 2009). …”
Section: Discussionmentioning
confidence: 64%
“…This is clearly a presupposition of the numerous corporate and medical and health-care leadership development courses (McKimm and Swanwick 2011). Indeed, just as the newly discovered need for medical leadership often goes without saying, many articles describing such courses do not bother to justify the claim that leadership can be learned (Crites, Ebert, and Schuster 2008;Goldstein et al 2009;O'Connell and Pascoe 2004;Varkey et al 2009). This notion of competency is also consistent with the concept of transformational leadership, with its contingent, flexible, and situational identification of appropriate leaders for different settings.…”
Section: Types Of Medical Leadershipmentioning
confidence: 96%